Dream Things True: Nonviolent Movements as Applied Consciousness - DuVall, Jack (Cosmos and History: The Journal of Natural and Social Philosophy, 2014)
<!–[if gte mso 9]> <![endif]–>Nonviolent movements have become a new form of human agency. Between 1900 and 2006, more than 100 such movements appeared, and more than half were successful in dissolving oppression or achieving people’s rights. Movements self-organize to summon mass participation, develop cognitive unity in the midst of dissension, and build resilient force on the content of shared beliefs. Some movements may even be a new venue for consciousness that "grows to something of great constancy" as Shakespeare said about "minds transfigured so together." <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–><!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>